Infecções por micobactérias atípicas. - R S Sarmento e Castro; O Vasconcelos; A A Horta; F Rodrigues; M F Pereira; A Rocha-Marques (Acta Médica Portuguesa, 1999)
The isolation of nontuberculous mycobacteria was considered for many years as a result of contamination or transient colonization. The role of these bacteria in human disease was recognized only after 1950. They were present almost exclusively in patients with underlying pulmonary pathology and were rare. The prevalence of disease caused by nontuberculous mycobacteria was dramatically increased with the AIDS epidemic. Disseminated infection with MAC and other atypical mycobacteria is nowadays a frequent complication of AIDS. The authors describe some epidemiological and clinical features of these nontuberculous mycobacteria emphasizing the role of MAC and make some considerations about the diagnosis, prophylaxis and treatment of these diseases. The authors end by presenting their own clinical experience.